Analisis Pertimbangan Hakim terhadap Pemberian Dispensasi Kawin tanpa Adanya Alasan Mendesak berdasarkan Perma Nomor 5 Tahun 2019 tentang Pedoman Mengadili Dispensasi Kawin: (Studi Penetapan Nomor 442/Pdt.P/2023/Pa.Krw) - Erlangga, Romi; Lia Amaliya; Muhamad Abas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Child marriage remains a significant issue in legal practice in Indonesia, despite the establishment of a minimum age requirement under Law Number 16 of 2019. In practice, the mechanism of marriage dispensation is often utilized without fulfilling the standard of “urgent reasons” as required by statutory regulations. This study aims to analyze the meaning of “urgent reasons” in granting marriage dispensation and to examine the judge’s considerations in Decision Number 442/Pdt.P/2023/PA.Krw based on Supreme Court Regulation Number 5 of 2019. This research is a normative legal study employing statutory and case approaches. Legal materials were obtained through library research and analyzed using a descriptive qualitative method with a deductive approach. The findings conclude that “urgent reasons” should be interpreted strictly as real and objectively verifiable emergency circumstances. However, in the decision, the judge granted the application without clear emergency conditions, relying instead on the prospective husband’s financial readiness and the child’s status as mukallaf. This indicates a discrepancy between legal norms and judicial practice, as well as the suboptimal application of the principle of the best interests of the child.